2021
DOI: 10.1038/s41435-021-00145-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin germline gene variation and its impact on human disease

Abstract: Immunoglobulins (Ig) play an important role in the immune system both when expressed as antigen receptors on the cell surface of B cells and as antibodies secreted into extracellular fluids. The advent of high-throughput sequencing methods has enabled the investigation of human Ig repertoires at unprecedented depth. This has led to the discovery of many previously unreported germline Ig alleles. Moreover, it is becoming clear that convergent and stereotypic antibody responses are common where different individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 136 publications
0
40
0
7
Order By: Relevance
“…Variability in escape patterns suggests that a diversity of antibodies are targeting these epitopes. Intra-species germline diversity in immunoglobulin genes may help explain why individuals with similar exposures often mount distinct responses [ 79 , 80 ]. On the other hand, escape profiles were more consistent in the SH-H, where the responses of convalescent macaques and vaccinated humans appeared to converge.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in escape patterns suggests that a diversity of antibodies are targeting these epitopes. Intra-species germline diversity in immunoglobulin genes may help explain why individuals with similar exposures often mount distinct responses [ 79 , 80 ]. On the other hand, escape profiles were more consistent in the SH-H, where the responses of convalescent macaques and vaccinated humans appeared to converge.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different expression levels of various genes could be promoted by variation within non-coding regions such as promoters, 5’UTRs and leader sequences, introns, or recombination signal sequences. Polymorphisms within these regions have been suggested to influence V(D)J gene expression levels within B-cell receptor repertoires ( Mikocziova et al, 2021 ). We also observed that variation in the MHC locus is associated with V-gene usage biases for productive TCRs, but not non-productive TCRs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly demonstrate how variation in V(D)J recombination-related genes can bias TCR repertoire combinatorial and junctional diversity. In the case of B cells, genetically determined V(D)J gene usage biases within B-cell receptor repertoires have been linked to functional consequences for the overall immune response to specific antigens and, thus, an increased susceptibility to certain diseases ( Mikocziova et al, 2021 ). As such, the genetic TCR repertoire biases identified here lay the groundwork for further exploration into the diversity of immune responses and disease susceptibilities between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in escape patterns suggests that a diversity of antibodies are targeting these epitopes. Intra-species germline diversity in immunoglobulin genes may help explain why individuals with similar exposures often mount distinct responses [ 83 , 84 ]. On the other hand, escape profiles were more consistent in the SH-H, where the responses of convalescent macaques and vaccinated humans appeared to converge.…”
Section: Discussionmentioning
confidence: 99%